Changing Patterns In Tobacco Consumption Among Spanish Military Personnel Under Stressful Conditions. Issue 2 (1st June 2011) - Granda-Orive, José Ignacio de; López-Aguilar, JC; García-Río, F; Solano-Reina, S; Jiménez-Ruiz, CA; Roig-Vázquez, F
Abstract : Objective: A study is made to determine the prevalence of smoking and its variation over time in a group of Spanish military personnel (MP) under stressful conditions. Methods: A questionnaire specifically designed for this study was administered to the entire MP contingent assigned to Banghis province (Afghanistan) between July and October 2009. A descriptive analysis was made (p < 0.05, 95%CI). Results: The study sample comprised 254 MP (males 239; mean age 32 years (SD 9)). A total of 39.8% (95%CI; 33.7 – 45.8) were smokers, while 3.1% (95%CI; 1.0 – 5.3%) were former smokers. Regarding smoking habit before and at the end of deployment, one-half (50.5%) of the smokers declared that they smoked the same as before, 20.8% more than before, and 18.8% less than before. In turn, 5.9% of the smokers claimed to have started to smoke in the course of deployment, while 4% of the former smokers declared that they had quit smoking. The MP who quit smoking were younger than those who began to smoke (24 ± 5 vs 39 ± 9 years, p = 0.038). Moreover, the heavy smokers (≥ 15 cigarettes/day) reduced tobacco consumption, while the less heavy smokers increased the habit (p < 0.0001). Conclusions: The prevalence of daily smokers is high among MP. The majority of smokers smoke the same at the end of deployment. Those who quit smoking during the mission are significantly younger than those who begin to smoke. In turn, heavy smokers reduced their habit, while less heavy smokers increased smoking.